The Impact of Covid-19 on the Lives of Former Lagoi Bay Tourism Workers in Kota Baru Village, Teluk Sebong District - Renaldi Renaldi; Nanik Rahmawati; Marisa Elsera (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
In Indonesia, the Covid-19 virus entered and spread rapidly since early March 2020, causing many deaths in various countries. The government has made various efforts to prevent the virus from spreading widely. However, since the outbreak of the pandemic, the tourism sector has been greatly affected by the negative impacts of Covid-19. Although tourism is a sector that provides employment opportunities and helps reduce the unemployment rate, workers in this sector have been severely impacted with the loss of income to support their daily needs. Thus, this study aims to investigate the social changes that have occurred due to Covid-19 on the lives of former Lagoi Bay workers in Kota Baru Village, Teluk Sebong District, by utilizing Piotr Sztompka's theory of social change. The results indicate that the pandemic has had a significant impact on Lagoi Bay tourism workers, leading to various social changes in their daily lives.